Association of Thermoresponsive Diblock Copolymer PDEGMA-b-PDIPAEMA in Aqueous Solutions: The Influence of Terminal Groups - Škorňa, Adam; Selianitis, Dimitrios; Pispas, Stergios; Štěpánek, Miroslav (Polymers, 2024)
Aqueous solutions of a thermoresponsive diblock copolymer poly(di-[ethylene glycol] methyl ether methacrylate)-b-poly(2-[diisopropylamino] ethyl methacrylate) (PDEGMA-b-PDIPAEMA) were studied by static, dynamic and electrophoretic light scattering, small-angle X-ray scattering and differential scanning calorimetry. Thermoresponsive behavior of PDEGMA-b-PDIPAEMA was investigated at two pH values, pH = 2, at which the terminal carboxylic group of the PDEGMA chain and the PDIPAEMA block are protonated, and pH = 7, where the carboxyl terminal group is ionized while the PDIPAEMA block is partially deprotonated and more hydrophobic. Both at pH = 2 and 7, PDEGMA-b-PDIPAEMA copolymer underwent extensive association (the size of the aggregates was between 100 and 300 nm), indicating strong interchain interactions. While the measurements confirmed thermoresponsive behavior of PDEGMA-b-PDIPAEMA at pH = 7, no changes in the association with temperature were observed at pH 2 as the thermoresponsivity of PDEGMA was suppressed by hydrogen bonding between carboxylic groups and PDEGMA segments, as well as due to the increased hydrophilicity of the PDIPAEMA block. Fluorescence measurements with pyrene as a fluorescent probe showed that both at pH = 2 and pH = 7 the associates were able to solubilize hydrophobic substances.
Keywords: thermoresponsive polymers; pH-responsive polymers; association; block copolymers